Asciaporrectidae, a new family of Rotifera (Monogononta: Ploima) with description of Asciaporrecta arcellicola gen. et sp. nov. and A. difflugicola gen. et sp. nov. inhabiting shells of testate amoebae (Protozoa) - de Smet, Willem H. (Zootaxa, 2006)
A new family of monogonont rotifers, Asciaporrectidae, is proposed for Asciaporrecta arcellicola gen. et sp. nov., A. difflugicola gen. et sp. nov. and A. hyalina (Wulfert, 1939) comb. nov. for Pleurotrocha hyalina. The new family is characterized by its trophi organized for grasping, with long rod-shaped manubria bearing an axe-shaped head; unci lying in a plane perpendicular to the plane of the incus, with 2–3 large teeth and well developed subunci composed of 3–5 teeth; and the unci/subunci pivoting on the broad, not pointed tips of the flat rami. Asciaporrecta arcellicola gen. et sp. nov. has 3-teethed unci; rami tips straight cut off, slightly expanded outwardly; and right ramus bearing a series of small knobs on inner margin distally; inhabiting shells of live Arcella discoides Ehrbg. (testate amoebae). Asciaporrecta difflugicola gen. et sp. nov. has 2-teethed unci; rami tips blunt, concave, reinforced and knobbed inwardly; inner margins of rami smooth; inhabiting shells of live Difflugia spp. (testate amoebae).